The effectiveness of acupuncture in the treatment of Tourette syndrome in Chinese children: a systematic review and meta-analysis - Zhou, Qian-Qian; Li, Zi-Chen; Hu, Zhuo-Ya; Tang, Juan; Tang, Peng; Wu, Qi-Rui; Deng, Zhong-Qi; Ma, Wen-Bin; Lan, Lei (Frontiers in Public Health, 2025)
ObjectiveAs a prominent complementary and alternative therapy, acupuncture is widely used to treat Tourette syndrome in children. This review aims to evaluate its clinical efficacy and provide evidence-based support for acupuncture in pediatric Tourette syndrome.MethodsWe systematically searched six databases: China National Knowledge Infrastructure, Wanfang Database, VIP Information Chinese Journal Service Platform, PubMed, Cochrane Central Register of Controlled Trials, and Embase, from their inception to 10 April 2025. Randomized controlled trials comparing acupuncture alone versus medication, or acupuncture plus other treatments versus other treatments alone, for children tic disorder were included.ResultsThirty-two studies were included, with 2,201 participants. Acupuncture may be more effective in improving motor tics symptoms than dopamine agonist [WMD −3.04, 95% CI (−3.77, −2.31), RD 0.38 (0.29, 0.46)], slightly improving vocal tics [WMD −2.39, 95% CI (−3.51, −1.26), RD 0.21 (0.10, 0.35)] and overall condition [WMD −5.56, 95% CI (−7.28, −3.83), RD 0.05 (0.02, 0.09)], but having little difference in functional impairment [WMD −2.27, 95% CI (−3.58, −0.96), RD 0.14 (0.09, 0.20)]. Acupuncture may be more effective than blank treatment on basis of other therapies in improving motor tics [WMD −2.51, 95% CI (−3.54, −1.49), RD 0.31 (0.19, 0.41)] and vocal tics [WMD −2.56, 95% CI (−3.66, −1.45), RD 0.28 (0.15, 0.40)], but slightly improving functional impairment [WMD −2.91, 95% CI (−4.64, −1.19), RD 0.13 (0.05, 0.23)] and overall symptom severity [WMD −5.57, 95% CI (−7.47, −3.68), RD 0.11 (0.06, 0.17)].ConclusionChinese children with Tourette syndrome using acupuncture may experience more improvement in motor tics symptoms than those using dopamine agonist. Acupuncture combined with other therapies may bring Chinese children with Tourette syndrome symptom relief in motor tics and vocal tics more than those alone. All results are supported by low-quality evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023444312, identifier CRD42023444312.